Adaptive Contribution of Thyroid Hormones in Obesity - Fatih Ozcelik; Ali Imran Dastan; Halime Hanim Pence; Mehmet Zahit Ciraci (International Journal of Negative Results, 2019)
Nowadays, obesity is seriously threatening healthy life in all societies, especially in developed societies. Obesity is showing its likely effects through biologically active substances called adipokines. The most familiar of these is leptin. Leptin is synthesized in directly proportional to the amount of adipose tissue and reduced appetite by stimulating the satiety center. This status is like a protective mechanism that tries to reverse severe pathological process. Similar to this behavior of leptin, thyroid hormones are increasing in the advanced stages of obesity, increasing the resting energy expenditure (REE). The accelerating oxidative phosphorylation causes the use of energy as heat, the energy that has not transformed into ATP, together with ATP synthesis. This situation, the significant portion of energy provides to consumed instead of storing as fat. In addition, finding that T3 accelerates glucose transport and the TCA cycle without changing the rate of ATP synthesis in skeletal muscles suggests that thyroid hormones may be an effective tool in standing against obesity. In addition of that, the presence of studies indicating that thyroid hormones have an increasing tendency in the advanced stages of obesity is likely thought to be a rescuer mechanism to increase the effectiveness of suppressed thyroid hormones. On the contrary of these ideas, having been reported suppressing 5’-deiodinease enzyme activity in chronic diseases causes anxiety about the effectiveness of thyroid hormones in obesity. Based on available information, we aimed to prepare a review evaluating of this adaptive condition of thyroid hormones.
Keywords: Obesity